Ruptured clear cell carcinoma of the ovary presenting as acute abdomen - Zhou, Zhen Ni (Gynecol Oncol Rep, 2016)
BACKGROUND: Ovarian cancer remains one of the leading causes of cancer-related deaths among women. Clear cell ovarian carcinoma is a rare histologic subtype accounting for 5–10% of all epithelial ovarian cancers and is often associated with endometriosis. Patients generally present with vague abdominal and pelvic complaints. However, patients can present in the acute setting with pleural effusions, ascites, bowel obstructions, and deep vein thrombosis. CASE: A 54 year old woman presenting with an acute abdomen secondary to rupture of ovarian clear cell carcinoma. CONCLUSION: Ovarian clear cell carcinoma should remain in the differential diagnosis in a patient presenting with an acute abdomen and imaging suspicious for a gynecologic malignancy originating from the ovary.